EVALUATION OF THE IMPLEMENTATION OF ACADEMIC SUPERVISION PROGRAMS IN THE LEARNING PROCESS - HAKIM, Sherly Nur; KHULUQO, Ihsana El; BUNYAMIN, Bunyamin (JKP | Jurnal Kepemimpinan Pendidikan, 2024)
The aim of the research is to describe the evaluation of the Academic Supervision Program in the Learning Process. The supervision carried out is limited to fulfilling the administrative duties and functions of the principal and not yet improving and developing teacher professionalism. So that teacher motivation to improve performance, make improvements and develop themselves, especially in the learning process, is not yet optimal. This research uses the CSE-UCLA research model focused on four process stages, namely planning, process, formative and summative, suitable for use in evaluating learning programs at Kindergarten Pembina IV, Setu District, South Tangerang City. The results of academic supervision carried out include the following: (a) Understanding the concepts, principles and basic theories of creative, innovative learning (b) Guiding teachers in compiling the syllabus for each area of development (c) Guiding teachers in choosing and using strategies that can develop various student potentials, (d) Guiding teachers in carrying out learning activities (e) Guiding teachers in managing and developing knowledge with ICT. 2) Academic supervision with a mentoring method can provide a solution to the problems faced by teachers so far and is the right strategy to improve the quality of learning. 3) Evaluation of the academic supervision program including: a) Context Evaluation. b). Input Evaluation. c) Process Evaluation. d) Product Evaluation. 4) The impact of academic supervision carried out by the kindergarten head in increasing teacher creativity was obtained by information that: academic supervision planning includes activities in determining goals, objectives, organizing activities and determining time.